2007
DOI: 10.1097/jcp.0b013e31802dda4a
|View full text |Cite
|
Sign up to set email alerts
|

Paliperidone Extended-Release Tablets for Prevention of Symptom Recurrence in Patients With Schizophrenia

Abstract: We evaluated the efficacy of paliperidone extended-release (ER), an investigational psychotropic agent, in delaying symptom recurrence in adult patients with schizophrenia and its safety and tolerability. In this randomized, double-blind, placebo-controlled, multicenter study, patients' symptoms were stabilized during an 8-week run-in and a 6-week stabilization phases using open-label, flexibly dosed paliperidone ER (3-15 mg once daily, starting dose = 9 mg). The primary efficacy variable was the time of first… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
120
0
7

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 189 publications
(132 citation statements)
references
References 22 publications
5
120
0
7
Order By: Relevance
“…12 In several studies, tachycardia was one of the most common adverse events observed. 4,13 Boom and coll.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…12 In several studies, tachycardia was one of the most common adverse events observed. 4,13 Boom and coll.…”
Section: Discussionmentioning
confidence: 99%
“…2 In premarketing studies, paliperidone was similarly linked to several cardiac problems, including bradyarrhythmias (0.1-1%), tachyarrhythmias (12-14%), and Q-T interval prolongation (3-5%). 3,4,13 Atypical antipsychotics have a potential to lower seizure thereshold. 2 According to the FDA's Adverse Event Reporting System (AERS) several reports of seizures have been linked to risperidone therapy.…”
Section: Discussionmentioning
confidence: 99%
“…I risultati delle fasi di estensione in aperto a 52 settimane di questi tre studi [24] confermano le evidenze di efficacia e tollerabilità già rilevate a 6 settimane. Gli altri due studi della fase registrativa sono stati condotti l'uno nella popolazione anziana (con un disegno simile agli studi pivotal con l'eccezione della flessibilità del dosaggio, di un endpoint primario di sicurezza e tollerabilità, anziché di efficacia e della durata della fase di estensione pari a 24 settimane) [25], l'altro nella popolazione adulta schizofrenica per studiare l'effetto di paliperidone ER sulla prevenzione delle ricadute [26]. Di questo studio è stata recentemente presentata la fase di estensione [27].…”
Section: Paliperidone Erunclassified
“…Sulla base degli studi sopra descritti i principali vantaggi clinici osservati con l'utilizzo di paliperidone ER nei pazienti schizofrenici comprendono, da un punto di vista dell'efficacia: efficacia nel trattamento dei sintomi acuti della schizofrenia [29] con una rapida comparsa dell'effetto terapeutico (miglioramento della sintomatologia evidente già al 4° giorno di terapia) [30]; efficacia nel mantenere il controllo sintomatologico con un trattamento continuativo come evidenziato dalle fasi di estensione [24,27]; efficacia nel ritardare la comparsa di ricadute dopo un periodo di stabilizzazione [26];…”
Section: Paliperidone Erunclassified
“…Clinical research on schizophrenia has focused primarily on symptom-based outcomes [6][7][8][9] , but it fails to consider the spectrum of components related to mental health recovery. Examples of outcomes that go beyond symptom management include indicators such as a person's sense of self-direction, empowerment, and hope 10 .…”
Section: Introductionmentioning
confidence: 99%